2023
DOI: 10.3390/w15020334
|View full text |Cite
|
Sign up to set email alerts
|

Does Fipronil Affect on Aquatic Organisms? Physiological, Biochemical, and Histopathological Alterations of Non-Target Freshwater Mussel Species

Abstract: Fipronil is widely used against insects in agriculture and ectoparasites in domestic areas and veterinary medicine. However, fipronil may influence non-target species as a result of the contamination of aquatic ecosystems. The present study aimed to investigate the acute and sublethal effects of fipronil in freshwater mussels (Unio delicatus), a non-target species, with physiological, antioxidant action mechanisms and histopathological observations. The 96-h LC50 value of fipronil was found to be 2.64 (1.45–4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…The glutathione levels of digestive gland tissues were decreased in 7day exposure and increased in 21-day exposure. THCs are commonly used physiological/immunological parameter to assess the health status of mussels and indicator of the mussels to stressors such as pollutants, disease, and changes in environmental conditions [8], [9], [16], [19], [20]. In the current study, significant decreases in the THCs occurred with increasing exposure time to nanoparticles.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The glutathione levels of digestive gland tissues were decreased in 7day exposure and increased in 21-day exposure. THCs are commonly used physiological/immunological parameter to assess the health status of mussels and indicator of the mussels to stressors such as pollutants, disease, and changes in environmental conditions [8], [9], [16], [19], [20]. In the current study, significant decreases in the THCs occurred with increasing exposure time to nanoparticles.…”
Section: Resultsmentioning
confidence: 59%
“…The freshwater mussel Unio delicatus Lea, 1863 is one of the most common mussel species in large river basins in southwest-eastern Anatolia. Due to its distribution areas, it is an indicator species in biomonitoring, ecotoxicological and phylogenetic studies [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological analysis of the tissues from the liver, kidney, and heart was performed using the method devised by [3] Cui et al in 2009. The left tibia was removed, cleansed, and kept in boiling water for 10 minutes [4].…”
Section: Methodsmentioning
confidence: 99%
“…It's important to note that the impact of neonicotinoids is not limited to insects. Some studies have also suggested potential effects on non-target organisms, including birds, fish, and mammals [3]. However, the exact cellular mechanisms and long-term effects on these organisms are still being studied.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on the impact of FIP on freshwater mussels ( Unio delicatus ) showed that exposure to 0.264 and 0.528 mg L −1 for 48 h and 7 days can lead to significant alterations in gills and digestive tissues, such as degeneration or even necrosis [ 20 ]. Furthermore, the negative impact of FIP exposure was also obtained for liver cells that had major ultrastructural changes characterized by cytoplasmic disorganization, fat accumulation, and increased numbers of mitochondria, rough endoplasmic reticulum and Kupffer cells after 15, 25, and 50 mg kg −1 administered intraperitoneally to female Swiss mice ( Mus musculus ) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%